2019
DOI: 10.1373/jalm.2018.028415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Generation Automated Assay for 25-Hydroxy Vitamin D Based on Competitive Protein Binding

Abstract: Background The interest for vitamin D has exponentially increased testing demand for 25-hydroxy vitamin D [25(OH)D]. Consequently, many laboratories are switching from LC-MS/MS methods to automated, high-throughput immunoassays. One of the major potential issues with these assays has been the lack of cross-reactivity with 25(OH)D2. Methods We have evaluated the Roche Elecsys vitamin D total II assay for accuracy by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The first blood samples were not available for a simultaneous analysis with the second samples. We also explored the potential associations [9][10][11][12] with COVID-19 of ABO blood groups, ascertained by the gel test (ID-Card ABO/RhD, DiaMed GmbH, Bio-Rad Laboratories Switzerland) [13] and 25-hydroxy vitamin D [25(OH)D] levels, determined by electrochemiluminisence-based assay (Elecsys vitamin D total II Roche Diagnostic, Germany) [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first blood samples were not available for a simultaneous analysis with the second samples. We also explored the potential associations [9][10][11][12] with COVID-19 of ABO blood groups, ascertained by the gel test (ID-Card ABO/RhD, DiaMed GmbH, Bio-Rad Laboratories Switzerland) [13] and 25-hydroxy vitamin D [25(OH)D] levels, determined by electrochemiluminisence-based assay (Elecsys vitamin D total II Roche Diagnostic, Germany) [14].…”
Section: Methodsmentioning
confidence: 99%
“…1 CI = Confidence interval;2 Adjusted for age sex ABO, occupation current smoker physical exercise alcohol consumption; 3 Adjusted for sex ABO;4 Adjusted for ABO age;5 Adjusted for sex age 6. Adjusted for age ABO sex;7 Adjusted for age sex ABO occupation;8 Adjusted for age sex ABO current smoker physical exercise alcohol beverage; 9 NC = No computable;10 Adjusted for age sex ABO chronic illness current smoker physical exercise alcohol consumption assistance mass gathering events ≥ 2 and over;11 Adjusted for age, sex ABO occupation current smoker physical exercise alcohol consumption assistance mass gathering events ≥ 2 and over;12 Excluding participants with symptoms before 6 March or after 31 March 2020;13 Adjusted for age, sex, ABO, occupation, current smoker physical exercise alcohol consumption assistance mass gathering events ≥ 2 and over;14 Adjusted for age sex, ABO, chronic illness occupation 15. Adjusted by age, sex, body mass index, ABO, chronic illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma 25(OH) D concentration is a key marker of a patient’s vitamin D levels, which can be determined by competitive binding assays (Musteata & Musteata, 2011), radioimmunoassay (van den Ouweland, Beijers, Demacker, & van Daal, 2010), high‐ performance liquid chromatography (HPLC), automated immunoassays (Asif, Groboske, Leung, Yeo, & van Wijk, 2019) and liquid chromatography–tandem mass spectrometry (Higashi, Shimada, & Toyo'oka, 2010; van den Ouweland et al, 2010; van den Ouweland, Vogeser, & Bacher, 2013), which has become the “gold standard” for vitamin D plasma concentration measurements in recent years (Galior, Ketha, Grebe, & Singh, 2018). The analysis of 25(OH) D is technically demanding owing to its hydrophobic nature and strong protein binding.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the total annual cost of management of DFUs was estimated to exceed $1.32 billion 56 . Recently, a single‐center retrospective review in China showed that the total cost of DFUs management per patient was $6,217.80 in 2020, with an average of $3,228.20, and it has tended to increase year by year 57 . Thus, if adequate vitamin D concentrations were beneficial to the improvement of the state of wound healing, vitamin D supplementation, as a potential therapeutic for DFUs, would be a safe, economical, and widely available method to improve prognosis and reduce mortality among individuals with DFU.…”
Section: Discussionmentioning
confidence: 99%